Pengaruh Capital Intensity dan Earnings Management terhadap Agresivitas Pajak - Sriyani, Gina; Afriyenti, Mayar (Universitas Negeri Padang, 2024)
This study aims to determine how much influence the effect of capital intensity and earnings management against tax aggressiviness. The method used is descriptive quantitative and types of data used is secondary data. The population in this study are all property and real estate companies listed in Indonesia stock Exchange in 2018-2021. the sampling method of this research is purposive sampling with total sample in this study was 100 data and this study using SPSS versi 26. Based on the result of the study, it shows that capital intensity has positive and significant effect on tax aggressiveness. Earnings management has negative and significant effect the tax aggressiveness. Simultaneously the variabel of capital intensity and earnings management have significant against tax aggressiveness.